Analisis Penerapan ISO 9001:2015 di Rumah Sakit: Sebuah Narrative Literature Review - Adelia Hartika; Mutiara Fitridiani; Masduki Asbari (Journal of Information Systems and Management (JISMA), 2023)
The purpose of writing this article is a narrative literature review of 3 (three) articles that discuss the analysis of ISO 9001: 2015 implementation in hospitals, aiming to identify and summarize previously published articles without any criticism for the articles reviewed. The results of the review indicate that the Hospital makes quality improvements, performance improvements, and the application of risk is carried out continuously to maintain the quality of service with the standard indicator of the assessment is the ISO 9001 Quality Management System (QMS) certification: 2015. The implementation of Integrated Quality Management in the Hospital has been well implemented based on standard service procedures. Factors consisting of customer focus, leadership, HR involvement, process approach, continuous improvement, fact-based decision making, and relationships with stakeholders have a very good correlation to the ISO 9001 Internal Quality Audit: 2015. It is recommended that all parties involved in the Hospital's operational processes are expected to be able to improve and prioritize service quality in providing satisfaction to every patient who comes to visit the Hospital.